Regenerative Biology of the Spine and Spinal Cord - Jandial, Rahul; Chen, Mike Y. (Advances in Experimental Medicine and Biology, 2012)
Editors hope that Regenerative Biology of the Spine and Spinal Cord appeals to the nostalgic sentiments of investigators and intellectuals in that it can be held in hand and provide a broad survey of leading edge science. At the same time its chapters can be digitally acquired for those established in the field to refine particular knowledge interests or gaps. Most importantly, we ask the reader, whomever that may be, to peruse without prejudice as countless more chapters will have been written before total spinal regeneration is achieved.